The Effectiveness of Marriage Guidance for Prospective Bride in Building the Sakinah Household - Jufri, Jufri; Hannani, Hannani (Al-Iftah: Journal of Islamic studies and society, 2020)
This study discussed the effectiveness of Marriage Guidance for Prospective Brides in Building Sakinah Households in KUA Kec. Maritengngae, Sidrap Regency. This study aims to determine the effectiveness of marriage guidance for prospective brides in building sakinah households in KUA Kec. Maritengngae in Sidrap Regency. This study used descriptive qualitative research. Descriptive research, researchers go directly to the field or carried out in the field through observation, interviews, and documentation studies, in order to obtain clear and representative data. The results of this study indicated that 1) Implementation of marriage guidance (Bimwin) in the Maritengngae District of Sidrap Regency for the bride and groom in realizing a sakinah family is the first step to prepare the prospective bride and groom to navigate their new life , namely married life; 2) The concept of a sakinah household has several characteristics, namely: Standing on a solid foundation of faith, Fulfilling the mission of worship in life, Obeying religious teachings, loving and cherishing each other, Compact educating children and Contributing to the good of society, the nation and the country, and 3) The effectiveness of the implementation of marriage guidance in forming sakinah households in the Maritengngae District, Sidrap Regency, especially for the bride and groom, in its implementation is quite effective. Compact educating children and Contributing to the good of society, the nation and country.